Senso comum, ideologia e filosofia na constituição de conhecimento, consciência e prática política - Rosalio Silva, Deise (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2019)
The article deals with a set of concepts (common sense, good sense, folklore, ideology, religion and philosophy), which interconnected determine the extent of the a conception of ideology and an absolute historicist and humanistic perspective of the construction of the subject, knowledge and political praxis, in the of Gramsci’s optic. We are interested in understanding the complexity and degrees of distinct developments that express the dialectic between these formulations in the delineation of social relations and in the construction of hegemony. The analysis that Gramsci developed on the historical moment in which he lived would not be possible without the elaboration of concepts that determine the understanding of how reality is configured, including from the point of view of human formation and the constitution of knowledge, senses and action practice. Thus, with the gnosiological and philosophical renewal undertaken, Gramsci’s contribution is understood in the improvement of a historical materialist interpretation of social reality and, therefore, of the concrete possibility of a change from theoretical and political practice to social transformation. Keywords: Common Sense; Good Sense; Philosophy; Ideology.